Emotional disorders and their therapy in chronic low back pain - A. I. Isaikin; T. I. Nasonova; A. Kh. Mukhametzyanova (Неврология, нейропсихиатрия, психосоматика)
Chronic low back pain (CLBP) is the most common chronic pain syndrome that causes deterioration of the quality of life and disability. Anxiety and depressive disorders are significantly more common in patients with CLBP. The negative impact of CLBP on cognitive abilities and sleep was revealed. Treatment of patients with CLBP should be started with non-pharmacological methods, including an educational program, kinesiotherapy, and cognitive behavioral therapy. Antidepressants are prescribed for CLBP to reduce the severity of associated anxiety and depressive disorders, improve sleep and relieve pain. The efficacy and safety of sertraline (Serenatа) in CLBP, its additional neurochemical mechanisms of action due to its effect on dopamine reuptake, interaction with sigma receptors, low incidence of side effects, and high adherence of patients to therapy are discussed.